(untitled) (Al-Academy, 2024)
Utopia and dystopia appeared in many areas of life. Some design institutions tried to highlight and realize them in graphic applications, the cover of the magazine, which is considered one of the graphic applications. The first chapter in the current research was organized according to axes. The research problem in it was formulated according to the question: How were utopias and dystopias established in The magazine cover? The importance of the research was theoretical and practical, and the goal of the research was to identify utopias and dystopias and how to perpetuate them. The research moved into the cognitive boundaries of 2021 around the covers of the American magazine (THE WEEK) as an area of ​​research. The second chapter (theoretical framework) contained two axes. The first axis was entitled: (Types of Utopia and Dystopia). The second axis It was entitled (Constructive Methods for Utopia and Dystopia). The third chapter included an explanation of the methodology, choosing a sample, the research tool, and analyzing the sample, which amounted to (3) models in a (intentional - non-probabilistic) manner. The fourth chapter detailed the results, conclusions, recommendations and proposals, and the results that were branched out: The American magazine (THE WEEK) reported its planning of developments. The technology that occurred in the creation of ideas, and it was concluded: There is an administrative policy that directs the design work in many companies that are concerned with designing the magazine cover in presenting ideas that often raise questions in the public opinion. Then the researcher recommended benefiting from international design experiences in designing the magazine cover. It is necessary to know the methods of designers, and the truth The chapter proposes: The utopia of intellectual trends and their reflection on graphic applications. Then write references.